Prevalence Of Vitamin D Deficiency Related Laboratory Parameters Among Pregnant Women In Potheri, South India - PAULRAJ SATHISH,; RAMASAMY PADMA,; DORAISAMI BALAKRISHNAN, (International Journal of Pharma and Bio Sciences, 2015)
Vitamin D deficiency is known to cause complications in pregnancy. There is sparse data on the prevalence of hypovitaminosis D in pregnancy, in India. Our study was undertaken to fill this lacuna. 148 pregnant women were enrolled from SRM Medical College and Research Centre, Kattankulathur, India. Serum concentrations of 25-hydroxyvitamin D [25(OH)D3] and related laboratory parameters were measured. The mean 25(OH)D3 level in pregnant women was 19.05 ng/mL. Only 8 subjects (5.4%) had >30 ng/mL (sufficient). 47 (33.7%) had 20-30ng/mL (insufficiency), 79 (53.4%) had <20ng/mL (deficiency) and, 14 (9.4%) had <10ng/mL (severe deficiency). We also found that maternal 25OH-D was associated positively to calcium (r= 0.6951, p<0.001) and phosphorus (r= 0.6211, p<0.001) and negatively to alkaline phosphatase (r= –0.4086, p<0.001) and parathyroid hormone (r=0.7856, p<0.001) by Pearson’s correlation coefficient method. Thus, in our study, we found an alarming total prevalence of 94.6% of vitamin D deficiency and insufficiency, among pregnant women. There is a definite need for vitamin D supplementation, in pregnant women.